Influence of life satisfaction, peer relationships, self-image, parenting style and spirtuality on positive youth development among adolescents in Selangor Malaysia - Kiadarbandsari, Atefeh (2015)
The focus of this study is to examine the influence of life satisfaction, peer relationships, self-image, parenting style, and spirituality on Positive Youth Development (PYD) among 593 adolescents, ages 14 and 16 years old. PYD as a theoretical framework focuses on mutually influential relationships between individuals and contexts. Malaysia is planning to become a fully-developed country by the year 2020. Thus, adolescents are considered as a significant resource and should be nurtured to guarantee the supportable continuous growth of the country. While recent researchers have found PYD a pathway to self-thriving in Western societies, few studies have incorporated in Asian contexts. To address this paucity, the current study was primarily conducted to determine the relationship between life satisfaction, peer relationships, self-image, parenting style, and spirituality with PYD, and the most significance predictor of PYD among adolescent students of national secondary schools in Selangor. A total of 593 adolescents from four national secondary schools of Selangor participated using Multi-Stage Cluster sampling. Data was collected using self-administered questionnaire included Satisfaction with Life Satisfaction Scale,Inventory of Parent and Peer Attachment, Self-image consisted of two parts, namely,Physical Appearance and Personality/Social Acceptance, Parenting Style Inventory II,Daily Spiritual Experience Scale, and PYD-very short form. The findings revealed life satisfaction, peer relationships, self-image, authoritative parenting style, and spirituality were correlated positively and significantly with PYD. Furthermore, the regression analysis showed life satisfaction, peer relationships, authoritative parenting style, and spirituality explain a significant amount of the variance in the adolescents’ PYD in Malaysia. Life satisfaction was identified as the most significant predictor of PYD. The study thus, provides significance contribution on how life satisfaction could enhance adolescent PYD. Findings from this study may have significant implications. Theoretically, the findings may shed light on the influence of context for adolescents in Malaysia as these studies shown variable were found to be highly correlated with PYD. From a practical perspective, the findings may imply that any effort in helping parents,psychologist, practitioners, and policy makers. Future studies recommended including a vast sample of respondents from all of the states of Malaysia to ensure the generalizability of the findings in a wider context.